The impact of food prices on household welfare and poverty in rural Tanzania - Tukae Mbegalo; Xiaohua Yu (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2016)
The effects from the change in food prices on household welfare is a topical issue among policy makers and scholars in Tanzania. However, relatively little is known about the quantitative effects of rising food prices on household welfare and poverty. This paper intends to quantitatively assess the welfare implications of rising food prices in rural Tanzania, by using household budget data from 2008/2009 and 2010/2011. We analyse the food Engel curves using a semi-parametric approach. This has revealed that a quadratic parametric fit can approximate the non-parametric food Engel curves. We then estimate the complete demand system using the QUAIDS model, and calculate welfare and poverty indices. Our results indicate that net sellers tend to show an improvement in welfare and net buyers tend to show a loss in welfare due to a food price increase. The effect of rising food prices varies across household characteristics and by region. For example, poor households are more affected than middle-income and rich households. The food prices have a major impact on overall poverty and across households. In particular, the poverty effect is much stronger for poor households than for middle-income and rich households. However, in the long-run, the poverty headcount ratio declines across all households due to the substitution effect. Thus, reformulation of food policy to counterbalance intermediate and long-term food price shocks is crucial in achieving a reduction in poverty and food security. Polices, such as improving domestic agricultural markets and lifting tariffs on imported food, are instrumental in addressing these issues.
Keywords: 330; Food Engel Curves; Food Price; Net Benefit Ratio; Poverty; QUAIDS; Semi Parametric and Welfare